Millennial Employees’ Performance: The Role of Psychological Well-being and Work Engagement - Ahnaf, Hafiz Haikal; Eryandra, Alvin (SENTRALISASI, 2024)
This study aims to determine the effect of psychological well-being and work engagement partially and simultaneously on the performance of millennial generation employees. The method use a quantitative approach. Sampling using non-probability sampling technique through google form with a total of 367 millennial generation employee respondents who work in Jabodetabek. The psychological well-being was measured by Ryff's Psychological Well-being (RPWB) - NFSH totaling 18 items. Work engagement was measured by Utrecht Work Engagement Scale-9 (UWES-9) with a total of 9 items. Employee performance was measured by  Individual Work Performance Questionnaire (IWPQ) totaling 18 items. Data processing using Jamovi 2.4 software with multiple linear regression models. Hypothesis testing results show that psychological well-being variables has no effect on employee performance. While the work engagement variable has a positive effect on employee performance. Simultaneously, psychological well-being and work engagement have positive effect on employee performance of millennial generation in Jabodetabek by 6,55%.